An In-Depth Study of Kazuo Ishiguro’s ’Never Let Me Go’ - Saadoon Muttair, Basim (Thi Qar Arts Journal, 2024)
The current paper presents the intricacy of the novel "Never Let Me Go" by Kazuo Ishiguro. This work is a complex combination of themes such as memory, identity, love, loss, and the ethical impacts of scientific progress via cloning. A thorough evaluation of Ishiguro’s use of narrative tools, like first-person narrative, non-linear stories, and emotional distance, will show how such methods intensify the thematic import of the novel and give it a philosophical orientation. The narrative analysis focuses on the Hailsham educational system, social control techniques and the attempt by clones to define themselves despite the limited choices they can make. Comparing with other such books, the paper locates Ishiguro’s novel in a bigger literary context, highlighting its relevance in the discussions about human nature, ethics, and the risks associated with scientific advances. The last part reveals the novel’s powerful take on how to treasure life, look into human relationships, and fight as humans to find a sense of purpose and meaning, even amid loss and fate.